High Accuracy Analysis of the Wilson Element (Journal of Computational Mathematics, 1999)
In this paper, the Wilson nonconforming finite element is considered for solving a class of second-order elliptic boundary value problems. Based on an asymptotic error expansion for the Wilson finite element, the global superconvergences, the local superconvergences and the defect correction schemes are presented. \u00a0
Keywords: Finite elements; Defect correction; Global super convergence Wilson element.